Gold–silver nanoshells promote wound healing from drug-resistant bacteria infection and enable monitoring via surface-enhanced Raman scattering imaging. (March 2020) - He, Jian; Qiao, Yue; Zhang, Hongbo; Zhao, Jun; Li, Wanli; Xie, Tingting; Zhong, Danni; Wei, Qiaolin; Hua, Shiyuan; Yu, Yinhui; Yao, Ke; Santos, Hélder A.; et al.
Abstract: Chronic infections, caused by multidrug-resistant (MDR) bacteria, constitute a serious problem yet often underappreciated in clinical practice. The in situ monitoring of the bacteria-infected disease is also necessary to track and verify the therapeutic effect. Herein we present a facile approach to overcome the above challenges through a Raman tag 3, 3′-diethylthiatricarbocyanine iodide (DTTC)-conjugated gold-silver nanoshells (AuAgNSs). With a strong responsive of the near-infrared laser due to surface plasmon resonance (SPR) from hybrid metallic nanoshell structure, AuAgNSs exhibits an efficient photothermal effect, and it simultaneously releases silver ions during laser irradiation to bacterial eradicate. Herein, two MDR bacteria strain, methicillin-resistant Staphylococcus aureus (MRSA) and extended-spectrum β-lactamase Escherichia coli, are chosen as models and studied both in vitro and in vivo. As a result, the AuAgNSs-DTTC substrates enable surface-enhanced Raman scattering imaging to provide a non-invasive and extremely high sensitive detection (down to 300 CFU mL −1 for MRSA) and prolonged tracking (at least 8 days) of residual bacteria. In a chronic MRSA-infected wound mouse model, the AuAgNSs gel-mediated photothermal therapy/silver-release leads to a synergistic would healing with negligible toxicity or collateral damage to vital organs. These results suggest that AuAgNSs-DTTC is a promising anti-bacterial tool for clinical translation. Graphical abstract: 3, 3′-diethylthiatricarbocyanine iodide (DTTC)-conjugated gold-silver nanoshell (AuAg) nanosystems are fabricated to enable surface-enhanced Raman scattering imaging and photothermal eradication to multidrug-resistant bacteria. Remarkably, the designed nanostructures provide a non-invasive and highly sensitive detection (down to 300 CFU mL −1 for MRSA) and prolonged tracking (at least 8 days) of residual bacteria during wound healing. Image 1